Apresentação do Dossiê "Linguagens e metodologias na Educação Geográfica" - Nascimento, Rosemy da Silva; Silva, Adilson Tadeu Basquerote; Nunes, Sérgio Claudino Loureiro; Seemann , Jörn (PerCursos, 2025)
Apresentação do Dossiê "Linguagens e metodologias na Educação Geográfica"